HUBUNGAN ANTARA MINAT DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BIOLOGI - Repa Septia Ratiana; Pramudiyanti Pramudiyanti; Berti Yolida (Universitas Lampung, 2014)
The objective of this research was to know the correlation between students’ interest and learning motivation toward biology learning product on the subject at SMAN 1 Way Tuba. The subjects of the research were the students of grade X that were chosen based on purposive sampling technique. The interest and learning motivation data were taken from questionnaire, while the learning product data was taken from block test. The data was analyzed using simple correlation (bivariate pearson) and double correlation. The result showed that there was a correlation between interest and learning product with the correlation grade 0.628 that categorized as strong, there was a correlation between learning motivation and learning product with the correlation grade 0.716 that categorized as strong, there was a correlation between interest and learning motivation 0.817 that categorized as strong. So, the interest and learning motivation have correlation with learning product, as good as the interest and motivation students, the learning product would be good.Penelitian ini bertujuan mengetahui hubungan antara minat dan motivasi belajar dengan hasil belajar biologi siswa SMA N 1 Way Tuba. Subyek pada penelitian ini siswa kelas X yang dipilih berdasarkan teknik purposive sampling. Data minat dan motivasi belajar diambil dari angket, sedangkan data hasil belajar diambil dari tes uji blok. Data dianalisis menggunakan korelasi sederhana (bivariate pearson) dan korelasi ganda. Hasil penelitian menunjukan ada hubungan antara minat dengan hasil belajar dengan angka korelasi 0,628 berkategori kuat, ada hubungan antara motivasi belajar dengan hasil belajar dengan angka korelasi 0,716, berkategori kuat, ada hubungan antara minat dan motivasi belajar dengan hasil belajar dengan korelasi 0,817 berkategori kuat. Jadi, minat belajar dan motivasi belajar dengan hasil belajar memiliki hubungan, semakin baik minat dan motivasi belajar siswa maka semakin baik hasil belajar yang diperoleh siswa.Kata kunci : biologi, hasil belajar, minat, motivasi belajar